2018
DOI: 10.1002/ppul.23993
|View full text |Cite
|
Sign up to set email alerts
|

Point of care diaphragm ultrasound in infants with bronchiolitis: A prospective study

Abstract: This study described ultrasound diaphragmatic values of previously healthy infants with bronchiolitis. DE, IS, and TEI correlated with outcome. If confirmed in larger studies, bedside ultrasound semiology of the diaphragm can be a new objective tool for the evaluation and outcome prediction of infants with bronchiolitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 68 publications
(164 reference statements)
2
71
5
Order By: Relevance
“…Several studies demonstrated diagnostic accuracy with sensitivities ranging from 40% to 100% and specificities ranging from 44% to 100%. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Despite these variations in sensitivities and specificities, recent studies 31 and metanalyses 24 have shown very promising results on lung US accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated diagnostic accuracy with sensitivities ranging from 40% to 100% and specificities ranging from 44% to 100%. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Despite these variations in sensitivities and specificities, recent studies 31 and metanalyses 24 have shown very promising results on lung US accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The amplitude of excursion of the hemidiaphragm is measured on the vertical line drawn from the baseline to the point of the maximum height of the inspiration 26 . This vertical distance represents right/diaphragmatic excursion 22 . Different ultrasound examinations were done and we recorded the average of three respiratory cycles.…”
Section: Methodsmentioning
confidence: 99%
“…Ultrasonography examinations were performed following the previously described methodology. [12][13][14][15] Longitudinal and transverse sections were collected on the anterior, lateral, and posterior chest wall. Images and clips were stored and archived.…”
Section: Performance Of Lusmentioning
confidence: 99%